Issues on waqf land registration process in Malaysia and improvement proposals - Ghazali, Noor Azimah; Sipan, I.; Raji, Fauziah; Mohammad, Mohammad Tahir Sabit (UTM Press, 2019)
Religious aspect of charity is connected closely with Islamic endowment (waqf plural awqaf) and becomes a key Islamic institution within the Muslim world for more than a millennium. Globally including Malaysia, waqf widely relates to land and buildings. Under Islamic Law the land or any property declared by individuals to become waqf is considered binding and valid as soon as the donor implies or expresses the intention clearly. There are 5 valid elements (rukn) of waqf declaration under Islamic Law. However, under Malaysian Land Law, waqf properties need to be registered at Land Office after a waqf declaration at State Islamic Religious Council (SIRC). The rational is to ensure land indefeasible ownership under National Land Code (NLC) 1965. However, there are few issues in the procedure existed. Therefore, this paper highlights nine issues from organisation and the donors involved in registration process of waqf land and suggesting nine improvement proposals by State Islamic Religious Council Johor. The approach adopted is ‘Content Analyses and ‘System Approach’.